PENGARUH KEAKTIFAN MENGIKUTI LAYANAN BIMBINGAN KELOMPOK TERHADAP KEPERCAYAAN DIRI SISWA KELAS XI IPA DI SEKOLAH MENENGAH ATAS NEGERI 12 PEKANBARU - SUCI LIA SARI; RIKA DEVIANTI (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2018)
This research studies the correlation. The subject of this study students 'high school science class XI Pekanbaru District 12 and the object of this study is the influence of active service following the guidance of a group of XI grade students' self confidence Natural Science State Senior High School 12 Pekanbaru. The study population was a class XI science students who had attended group counseling services, amounting to 40 people. Given the population is so large, the writer uses Total Sampling. Techniques used to collect data a questionnaire prepared following the Likert scale. Once the data is collected and then analyzed by Product Moment correlation with the formula. Based on the data analysis can be concluded that (1) active service following the guidance of the class XI science students State SeniorÂ High School 12 Pekanbaru is located in the category of being which is equal to 76 316%. (2) confidence class XI science students State Senior High School 12 Pekanbaru is located in the category of 67.5%. (3) Based on the obtained correlation test correlation coefficient of 0703. The results of these correlation coefficients indicate that there are significant effect between self-esteem class XI science student State Senior High School 12 Pekanbaru. Effect of active service following the guidance of the group of XI grade students' self confidence Natural Science State Senior High School 12 Pekanbaru obtained from the coefficient of determination was 49%. Keyword:Â